A highly enantioselective Friedel–Crafts reaction of 3, 5-dimethoxylphenol with nitroolefins mediated by a bifunctional quinine derived thiourea catalyst. Issue 16 (6th April 2017) - Han, Xiaoyu; Ye, Can; Chen, Fenfen; Chen, Qu; Wang, Yongjiang; Zeng, Xiaofei
Abstract : A useful and highly enantioselective Friedel–Crafts reaction of 3, 5-dimethoxylphenol with nitroolefins catalyzed by a bifunctional quinine derived thiourea catalyst was developed. Abstract : A useful enantioselective Friedel–Crafts reaction of 3, 5-dimethoxylphenol with nitroolefins catalyzed by a bifunctional quinine derived thiourea catalyst9 was developed. The Michael addition products could be obtained in good to high yields (68–92%) and with excellent enantioselectivities (89–98% ee). Such a reaction is exceptionally attractive in virtue of its simple protocol, ready availability of the starting materials, and practical applications of the products.